Comment: Paper on the progress of pure mathematics "proof of 3x + 1 conjecture" - Xie, Ling (Annals of Mathematics and Physics, 2024)
The unresolved problem in number theory: the 3x+1 problem, deeply loved by math enthusiasts. I saw a paper titled "Proof of 3x+1 Conjecture" in the Journal of Pure Mathematical Progress (ISSN Print: 2160-0368), and its proof was incorrect.